Factor the expression. 30x2 + 65x + 25

30x^2 + 65x + 25 = 5(6x^2 + 13x + 5); = 5(2x + 1)(3x + 5)

Question

Asked 11/30/2014 7:20:56 PM

Updated 12/1/2014 5:01:45 AM

1 Answer/Comment

s

Rating

8

30x^2 + 65x + 25

= 5(6x^2 + 13x + 5);

= 5(2x + 1)(3x + 5)

= 5(6x^2 + 13x + 5);

= 5(2x + 1)(3x + 5)

Added 12/1/2014 5:01:45 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [12/1/2014 5:09:35 AM]

Select the product of (-6x7y)(x3y5)

Question

Not Answered

Updated 11/24/2014 6:08:25 AM

1 Answer/Comment

(-6x^7y)(x^3y^5)

= -6x^7*x^3*y^5*y

= -6x^10y^6

= -6x^7*x^3*y^5*y

= -6x^10y^6

Added 11/24/2014 6:08:25 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/28/2014 1:57:22 AM], Rated good by andrewpallarca

Select the product of (5x - 4)(5x + 9).
25x2 - 25x - 36
50x - 36
25x2 + 25x - 36
10x + 5 **Weegy:** (5x + 1)? **User:** Select the product of (5x - 4)(5x + 9).
a. 25x2 - 25x - 36
b. 50x - 36
c. 25x2 + 25x - 36
d. 10x + 5 **Weegy:** (5x + 1)? **User:** (x + 4)3 (More)

Question

Updated 11/23/2014 11:37:33 PM

2 Answers/Comments

(5x - 4)(5x + 9)

= 5x*5x - 4*5x + 5x*9 - 4*9

= 25x^2 - 20x + 45x - 36

= 25x^2 + 25x - 36

= 5x*5x - 4*5x + 5x*9 - 4*9

= 25x^2 - 20x + 45x - 36

= 25x^2 + 25x - 36

Added 11/23/2014 11:34:57 PM

This answer has been confirmed as correct and helpful.

Rated good by andrewpallarca, Confirmed by andrewpallarca [11/24/2014 2:10:54 AM]

(x + 4)^3

= (x + 4)(x + 4)(x + 4)

= (x^2 + 8x + 16)(x + 4)

= x^3 + 8x^2 + 16x + 4x^2 + 32x + 64

= x^3 + 12x^2 + 48x + 64

= (x + 4)(x + 4)(x + 4)

= (x^2 + 8x + 16)(x + 4)

= x^3 + 8x^2 + 16x + 4x^2 + 32x + 64

= x^3 + 12x^2 + 48x + 64

Added 11/23/2014 11:37:33 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/24/2014 2:11:40 AM], Rated good by andrewpallarca

the product of (3x - 9)(3x - 9).

Question

Not Answered

Updated 11/24/2014 6:52:32 AM

1 Answer/Comment

(3x - 9)(3x - 9)

= 3x*3x - 9*3x - 3x*9 + (-9)*(-9)

= 9x^2 - 27x - 27x + 81

= 9x^2 - 54x + 81

= 3x*3x - 9*3x - 3x*9 + (-9)*(-9)

= 9x^2 - 27x - 27x + 81

= 9x^2 - 54x + 81

Added 11/23/2014 11:33:22 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/24/2014 6:52:27 AM]

simplify 64w^2 -64w-16w+16

Question

Updated 11/23/2014 6:08:26 PM

1 Answer/Comment

64w^2 - 64w -16w+16

= 64w^2 - 80w + 16

= 16(42^2 - 5w + 1)

= 16(4w - 1)(w - 1)

= 64w^2 - 80w + 16

= 16(42^2 - 5w + 1)

= 16(4w - 1)(w - 1)

Added 11/23/2014 6:08:26 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/24/2014 5:43:17 AM]

simplify this 64w^2 -64w-16w+16

Question

Not Answered

Updated 11/23/2014 6:55:56 PM

1 Answer/Comment

64w^2 -64w-16w+16

=64w(w-1)-16(w-1)

=(w-1)(64w-16)

=16(w-1)(4w-1)

=64w(w-1)-16(w-1)

=(w-1)(64w-16)

=16(w-1)(4w-1)

Added 11/23/2014 6:55:56 PM

This answer has been confirmed as correct and helpful.

34,448,482

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 612 [Total 6485] Ratings 11 Comments 502 Invitations 0 Offline

There are no comments.